2023
DOI: 10.1177/13670069221126272
|View full text |Cite
|
Sign up to set email alerts
|

“I feel really special and proud that I am bilingual”: Exploring a second-generation Korean American bilingual adolescent’s emotions and sense of belonging through family language policy

Abstract: Aims and objectives: The purpose of this exploratory case study is to contribute to the set of studies that center children’s perspectives on their bilingual development, with a specific focus on their emotional connection within their linguistic family landscape. Methodology: This was a case study of a Korean transnational family in the United States and included both parents and their daughter. Data and analysis: Due to COVID-19 restrictions, semi-structured in-depth interviews and a language-mapping activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…While parental attitudes (Jo et al., 2023) and emotions such as anxiety (Sevinç, 2022) may be transmitted to children in HL maintenance, scholars emphasize that children's emotional experiences are independent from those of their parents (Blackledge & Creese, 2008; De Houwer, 2015; Wilson, 2020). In French–English bilingual families in the United Kingdom, Wilson (2020) found that children felt annoyed about their FLP, but tended to accept parental language strategies, whereas parents positively described their children's bilingual experience as “organic,” “normal,” or “natural.” In other studies, parents reported their feeling of frustration caused by children's resistance (Wang, 2023), whereas children pointed to their parents’ ways of forcing the FLP as the source of their anxiety (Sevinç, 2022).…”
Section: Emotional Experiences Of Mothers and Children In Heritage La...mentioning
confidence: 99%
“…While parental attitudes (Jo et al., 2023) and emotions such as anxiety (Sevinç, 2022) may be transmitted to children in HL maintenance, scholars emphasize that children's emotional experiences are independent from those of their parents (Blackledge & Creese, 2008; De Houwer, 2015; Wilson, 2020). In French–English bilingual families in the United Kingdom, Wilson (2020) found that children felt annoyed about their FLP, but tended to accept parental language strategies, whereas parents positively described their children's bilingual experience as “organic,” “normal,” or “natural.” In other studies, parents reported their feeling of frustration caused by children's resistance (Wang, 2023), whereas children pointed to their parents’ ways of forcing the FLP as the source of their anxiety (Sevinç, 2022).…”
Section: Emotional Experiences Of Mothers and Children In Heritage La...mentioning
confidence: 99%